Influence of MWCNT Loading and Structural Configuration on the Performance of PDMS-Based Triboelectric Nanogenerators - Ahmed, Manal Ahmed (AUC Knowledge Fountain, 2026)
This thesis investigates the development and performance enhancement of triboelectric nanogenerators (TENGs) through the systematic fabrication of nanocomposites comprising polydimethylsiloxane (PDMS) and multiwalled carbon nanotubes (MWCNTs). With increasing global demand for sustainable and renewable energy sources, TENGs have emerged as promising devices for harvesting mechanical energy from everyday activities. The thesis aims to explore how varying concentrations of MWCNTs and their aspect ratio affect the electrical output performance of PDMS‑based TENGs. Composite films with thicknesses ranging from 0.75 mm to 1.25 mm and MWCNT loadings of 0 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, and 0.4 wt% were fabricated via a solution‑mixing technique. In addition, a sandwich‑structured TENG configuration was developed by embedding MWCNT buckypaper layers with varying MWCNTs loadings (25 mg and 35 mg), produced by vacuum filtration, within the PDMS matrix to establish continuous charge‑transport networks and enhance conductivity. The results show that a 0.75 mm‑thick composite containing 0.2 wt% MWCNTs delivers the highest performance among the single‑layer films, with high‑aspect‑ratio MWCNTs producing a peak‑to‑peak voltage of 376 V and low‑aspect‑ratio MWCNTs yielding 312 V, compared to 114 V for pure PDMS at the same thickness. Building on this, the influence of a buckypaper‑based sandwich structure was assessed in 1.25 mm films by inserting buckypaper as a middle layer either between neat PDMS or between 0.2 wt% high‑aspect‑ratio MWCNT/PDMS composite layers. A 25 mg buckypaper interlayer within the 0.2 wt% MWCNT/PDMS composite achieved an average peak‑to‑peak voltage of 389 V, outperforming all other configurations and corresponding to an improvement of approximately 94.5% relative to the 1.25 mm composite film without buckypaper and about 455% relative to pure PDMS. In contrast, increasing the buckypaper mass to 35 mg led to reduced output, indicating that excessive buckypaper loading introduces additional losses. Overall, the integration of MWCNTs and the optimized 25 mg buckypaper–PDMS sandwich architecture significantly enhances voltage generation efficiency, underscoring the potential of these engineered composites for advanced TENG applications.